Fast, iterative image reconstruction for MRI in the presence of field inhomogeneities. - Sutton, B.P.
In magnetic resonance imaging, magnetic field inhomogeneities cause distortions in images that are reconstructed by conventional fast Fourier transform (FFT) methods. Several noniterative image reconstruction methods are used currently to compensate for field inhomogeneities, but these methods assume that the field map that characterizes the off-resonance frequencies is spatially smooth. Recently, iterative methods have been proposed that can circumvent this assumption and provide improved compensation for off-resonance effects. However, straightforward implementations of such iterative methods suffer from inconveniently long computation times. This paper describes a tool for accelerating iterative reconstruction of field-corrected MR images: a novel time-segmented approximation to the MR signal equation. We use a min-max formulation to derive the temporal interpolator. Speedups of around 60 were achieved by combining this temporal interpolator with a nonuniform fast Fourier transform with normalized root mean squared approximation errors of 0.07%. The proposed method provides fast, accurate, field-corrected image reconstruction even when the field map is not smooth.
Keywords: MR signal equation; MRI; Fast iterative image reconstruction; Field map; Field-corrected MR images; Image distortions; Magnetic field inhomogeneities; Magnetic resonance imaging; Min-max formulation; Noniterative image reconstruction methods; Nonuniform fast Fourier transform; Normalized root mean squared approximation errors; Off-resonance frequencies; Spatially smooth field map; Temporal interpolator; Time-segmented approximation